2008
DOI: 10.1074/jbc.m803923200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Divergence between Co-chaperones of Hsc70

Abstract: The ATPase cycle of the chaperone Hsc70 is regulated by co-chaperones; Hsp40/DnaJ-related proteins stimulate ATP hydrolysis by Hsc70 and can bind unfolded polypeptides themselves. Conversely, various nucleotide exchange factors (NEFs) stimulate ADP-ATP exchange by Hsc70. We analyzed the purified Hsp40-related co-chaperones DJA1 (Hdj2) and DJA2 (Hdj3) and found that they had a distinct pattern of binding to a range of polypeptides. DJA2 alone could stimulate Hsc70-mediated refolding of luciferase in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 44 publications
7
83
2
Order By: Relevance
“…1A). ATPase activity of purified His-Hsc70 was 0.36 min ÏȘ1 in the absence of Hdj-2 and 0.96 min ÏȘ1 in the presence of both Hdj-2 and CBag, in good agreement with previous studies (15,48).…”
Section: His and Gst Tag Protein Expression And Purificationsupporting
confidence: 80%
See 1 more Smart Citation
“…1A). ATPase activity of purified His-Hsc70 was 0.36 min ÏȘ1 in the absence of Hdj-2 and 0.96 min ÏȘ1 in the presence of both Hdj-2 and CBag, in good agreement with previous studies (15,48).…”
Section: His and Gst Tag Protein Expression And Purificationsupporting
confidence: 80%
“…A BamHI and XhoI fragment of CBag (47,48) was generated by PCR and ligated into the same sites of pGEX4T.1 to obtain pGEX4T.1-CBag. All PCR-amplified sequences were confirmed by DNA sequencing.…”
Section: Plasmidsmentioning
confidence: 99%
“…Consistent with this hypothesis, comparative in vitro studies with mammalian homologs showed that certain Hsp70/JDP/NEF combinations work much better in FLuc folding than others and some not at all (Tzankov et al, 2008;Rauch and Gestwicki, 2014). How specific combinations select suitable clients is unknown.…”
Section: Involvement Of Nefs In Protein Folding and Importsupporting
confidence: 52%
“…The multiple J proteins of eukaryotes are believed to increase the ability of Hsp70 to recognize diverse substrates, albeit with some redundancy (31). Different eukaryotic J proteins produce varying effects on in vitro Hsp70 ATPase and refolding activities (32)(33)(34), or can act as holdases that prevent protein aggregation (35,36). Unique mixtures of J proteins can function as disaggregases (37,38).…”
Section: Significancementioning
confidence: 99%